Nanostructure and doping stimulated phase separation in high-ZT Mg2Si0.55Sn0.4Ge0.05 compounds. (15th January 2015) - Polymeris, G.S.; Vlachos, N.; Khan, A.U.; Hatzikraniotis, E.; Lioutas, Ch.B.; Delimitis, A.; Pavlidou, E.; Paraskevopoulos, K.M.; Kyratsi, Th.
Abstract: A study was attempted on the structural properties across all relevant length-scales for Mg2 (Si, Sn, Ge)-type solid solutions of the formula Mg2 Si0.55− y Sn0.40 Ge0.05 (Bi, Sb) y . The study focuses on three families of samples, namely one undoped compound, as well as two families of doped samples, one at Bi ( y  = 0.02) and one doped at Sb ( y  = 0.0125); the latter two materials were chosen because they yielded the highest ZT values. The results of the present study strongly suggest that, besides the main matrix and the MgO, there are three groups of secondary phases extending with uniform composition from nano-scale to macro-scale, as observed by high-resolution transmission electron microscopy (atomic scale), transmission electron microscopy (nano-scale), scanning electron microscopy coupled with energy-dispersive X-ray analysis (micro-scale) and X-ray diffraction (macro-scale): all these length-scale observations verified the presence of hierarchical structure extending down to a few nanometers, with uniform, narrow distribution of nano-particles, even in the case of MgO. Phase separation is strongly stimulated and modulated by doping.